Congos do Carmo, fé e devoção na festa de Nossa Senhora do Rosário - BARROS, Meyre Gomes (Universidade Federal do Tocantins, 2023)
The feast of Nossa Senhora do Rosário is permeated by numerous devotional manifestations, and in view of this, the study emerged from the need for greater knowledge involving a secular tradition of the Congos in the festive context of the feast. In this sense, one of the pillars of this project is to value the cultural manifestations of Monte do Carmo – TO, directly linked to the devotion and lineage of the Congo in the festivity of Senhora do Rosário. Its main objective is to support and underpin the traditional culture of the congada in the feast of Nossa Senhora do Rosário in Monte do Carmo, in how the tradition is filled with love and devotion for the Congos in their entirety since the generations. Having as methodological procedures the execution of a thorough bibliographic review with topics such as cultural geography, which is one of the pillars for the production of this project, and an interview conducted by the academic of this project to the Congos of Monte do Carmo - TO. Therefore, it can be concluded that the traditional and festive journey of the Congos rescued a strong cultural matrix, with many signs of a rich culture in dance, singing and in the elaboration of the plot, and that tradition and devotion are passed from generation to generation.